A Versatile Dual‐Emission Fluorescent Microhybrid Enabling Visual Detection of Glucose and Other Oxidases‐Based Biocatalytic Systems. Issue 2 (23rd April 2016) - Lu, Xiaohui; Wang, Peipei; Wang, Yucong; Liu, Chenghui; Li, Zhengping
Abstract : A novel kind of dual‐emission microhybrids (DEMBs) is rationally fabricated which allows facile visual detection of glucose in serum. Here, green‐emitting rhodamine‐embedded silica microbeads (MBs) are used as the core of the DEMBs while a shell of CdTe quantum dots of red fluorescence is attached on the surface of MBs as the signal report unit. The red fluorescence of CdTe is susceptible to H2 O2 produced by the glucose/glucose oxidase (GOD) reaction while the inner green fluorescence of the MBs is inert. Therefore, with the assistance of GOD, increased glucose levels can lead to variations of the two fluorescence intensity ratios of DEMBs accompanied with continuous color changes from red to green under a UV lamp, which can be easily and distinctly identified by naked eye. This DEMB‐based sensing strategy can be directly used for assaying glucose in serum and the results agree well with those measured by commercial glucose meter, indicating that this glucose sensing system is reliable for practical applications. More importantly, since many oxidases‐based enzymatic reactions can all produce H2 O2, the proposed design may serve as a generic platform for probing of H2 O2 ‐generating oxidases as well as their substrates. Abstract : A novel dual‐emission fluorescent microhybrid is rationally fabricated which to allow visual detection of glucose and other H2 O2 ‐generating biocatalytic reactions without the need of any expensive equipment. This simple and low‐cost strategy can help to preliminarily screen diabetic patients, particularly in some poor and backward territories, by just visual examination of blood glucose levels.